2017
DOI: 10.21276/apjhs.2017.4.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Serum ascorbic acid and alpha-tocopherol levels in bidi smokers and tobacco chewers

Abstract: Aim: To assess serum ascorbic acid and alpha-tocopherol levels in bidi smokers, tobacco chewers and tobacco nonusers. Materials and Methods: Forty smokers [25 subjects smoking ≤24 bidi /day (moderate) and 15 subjects smoking > 24 bidi/day (heavy) with a smoking habit of > 10 years, 20 subjects tobacco chewers ≥10 g tobacco/day) chewing for > 10 years] were included in the study.All selected subjects were normal with no symptoms of any disease. They were classified on the basis of age, BMI and with and without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(7 reference statements)
1
0
0
Order By: Relevance
“…In the present study we observed significant decrease in antioxidants like vitamin C and E in PMT users. Similar findings were reported by Bhimwal et al and Giraud et al [ 27 , 28 ]. Depletion of antioxidants is a risk factor for chronic diseases like cancer and coronary heart disease.…”
Section: Main Textsupporting
confidence: 92%
“…In the present study we observed significant decrease in antioxidants like vitamin C and E in PMT users. Similar findings were reported by Bhimwal et al and Giraud et al [ 27 , 28 ]. Depletion of antioxidants is a risk factor for chronic diseases like cancer and coronary heart disease.…”
Section: Main Textsupporting
confidence: 92%